2013
DOI: 10.1371/journal.pone.0081856
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Binding Protein and IL-6 Mark Paradoxical Tuberculosis Immune Reconstitution Inflammatory Syndrome in HIV Patients

Abstract: BackgroundTuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) remains a poorly understood complication in HIV-TB co-infected patients initiating antiretroviral therapy (ART). The role of the innate immune system in TB-IRIS is becoming increasingly apparent, however the potential involvement in TB-IRIS of a leaky gut and proteins that interfere with TLR stimulation by binding PAMPs has not been investigated before. Here we aimed to investigate the innate nature of the cytokine response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 38 publications
5
40
0
Order By: Relevance
“…It has been suggested that disturbances in the innate immune system [22] or in the interplay between the innate and adaptive immune system [11] could drive TB-IRIS pathogenesis. This is supported by repeated findings of elevated levels of IL-6 and TNFα, among other innate cytokines, during TB-IRIS [14], [16], [23][26]. Interestingly, elevated innate cytokine production has also been reported in TB-IRIS patients after toll-like receptor (TLR) 2 stimulation with lipomannan, a TB pathogen-associated molecular pattern (PAMP) [27].…”
Section: Introductionmentioning
confidence: 64%
“…It has been suggested that disturbances in the innate immune system [22] or in the interplay between the innate and adaptive immune system [11] could drive TB-IRIS pathogenesis. This is supported by repeated findings of elevated levels of IL-6 and TNFα, among other innate cytokines, during TB-IRIS [14], [16], [23][26]. Interestingly, elevated innate cytokine production has also been reported in TB-IRIS patients after toll-like receptor (TLR) 2 stimulation with lipomannan, a TB pathogen-associated molecular pattern (PAMP) [27].…”
Section: Introductionmentioning
confidence: 64%
“…Additionally, some control patients have rapid recovery of tuberculosisspecific T-cell function similar to TB-IRIS patients, but do not progress to IRIS [15][16][17]. In an exploratory analysis, we tested the hypothesis that increases in IL-6 levels, which have been associated with IRIS [11,13,15,20], would be less in control patients who also had rapid recovery of cellular immune function compared to TB-IRIS patients using previously determined IL-6 concentrations [15] and rank-sum tests. In this analysis, controls were restricted to those described in this study who had increases at week 4 of ART that were greater than the overall group median for IFN-γ + /IL-2 + /TNF-α + CD4 + T-cells, CD4 cell counts, and tuberculosis-specific IFN-γ responses by enzyme-linked immunospot (ELISpot) assay [15].…”
Section: Discussionmentioning
confidence: 99%
“…Immunologically, higher pre-ART levels of immune activation and rapid increases in tuberculosis-specific interferon gamma (IFN-γ)-producing cells after ART initiation in HIV-infected adults have been associated with development of TB-IRIS [7,[9][10][11][12]. However, in several recent studies, levels of pre-ART immune activation were actually lower in TB-IRIS patients vs controls [13][14][15], and multiple reports have indicated that patients without TB-IRIS may also have robust increases in levels of pathogen-specific immune responses on ART [16,17]. Existing data are therefore inconclusive about whether higher levels of pre-ART immune activation predispose to TB-IRIS and whether tuberculosis-specific T-cells are involved in TB-IRIS pathogenesis.…”
mentioning
confidence: 99%
“…Multiple studies have demonstrated rapid increases in pro-inflammatory cytokines in patients developing TB-IRIS, and immune enhancement with interventions other than ART could therefore be detrimental (7477). On the other hand, it is equally plausible that IL-7 or other cytokine therapy could decrease TB-IRIS risk if this risk is driven primarily by antigen load during ART, as suggested by data linking IRIS risk with a shorter interval between TB treatment and ART initiation (10, 12).…”
Section: Augmenting Pathogen-specific Immunity Versus Minimizing Riskmentioning
confidence: 99%